STRUCTURAL AND SEMANTIC ANALYSIS OF MARKETING- MANAGEMENT TERMS - Mansurova, Nodira (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to the allocation and analysis of frequency syntactic models for the formation of English-language multicomponent terminological units in the sphere of management and marketing. It is proved that within the framework of the investigated sublanguage is largely dominated by the syntactic way of education terms in comparison with the traditional for modern English terminological systems of affixation, word composition and abbreviation. It reflects the types of terms and the main structural ways of their nomination. It is also analyses Lexical units of a marketing and management belong to the main units of the statement (message).